Association between apolipoprotein E genotype, chronic liver disease, and hepatitis B virus - Ahn, Seun Joo (The Korean Association for the Study of the Liver, 2012)
BACKGROUND/AIMS: Apolipoprotein E (ApoE) plays an important role in regulating lipid and lipoprotein metabolism, and ApoE genotypes are known to affect plasma lipoprotein concentrations. We investigated whether ApoE genotype determines the disease outcome in hepatitis B virus (HBV)-infected individuals, and verified the association between ApoE genotype and the occurrence of hepatocellular carcinoma (HCC) in patients with chronic liver diseases of various etiologies. METHODS: This hospital-based, case-controlled study enrolled 156 subjects (47 healthy controls, 50 HBV-related liver cirrhosis patients, and 59 HCC patients). ApoE genotypes were determined using PCR-based ApoE genotyping kits. The biological significance of ApoE genotype was verified by measuring serum ApoE levels using an ELISA kits. RESULTS: The ε3 allele was the most common allele, with allele frequencies among the entire cohort of 5.8%, 84.3%, and 9.9% for the ε2, ε3, and ε4 alleles, respectively. Significantly more of those patients carrying the ε3/3 genotype had developed liver cirrhosis compared to the control subjects. Being an ApoE4 carrier was associated with a lower probability of developing liver cirrhosis. The allele frequencies and genotype distribution of ApoE did not differ significantly between the liver cirrhosis and HCC patients. The serum level of ApoE was significantly higher in patients with liver cirrhosis than in the healthy controls, but did not differ significantly with the ApoE genotype. CONCLUSIONS: The ApoE ε3/3 genotype frequency was higher in patients with HBV-associated liver cirrhosis than in the controls.